(3fRgI GdebdJjf aj SjQI GdOhdJjf GdYdGFjI hGdLdGFjIs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdfYe CeG HYO aEfi LeYJ ai cJGHjf Ke Efi CQOJ Gdhbha Ydi CNHGQ edci HdGO GdYLe ai ReGffG GdPjf bgQG GdYHGO s
(3BNQgG (B:s
(3jfJgi HPcQ gRjeI GdJJGQ HCQV MeU ai TgQ GdeMQe SfI (B659 (3Hbhdg (B: (3hdG JRGd JQO EdjfG ef CNHGQg eYge hLejY ef jhGabg ef edhc GdeSdejf s
(3GNJUQ GdeDda ef cJGH dTgGH GdOjf Hf CMeO Hf Ydi Hf eMeO GdfShi YdjgG Jedc hbQGAGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
Keywords: (3GdJGQjNs